CUSTOMER SATISFACTION OF SERVICES PROVIDED BY FRESH FRUIT BUNCH (FFB) COLLECTION CENTERS - Nazirah Che Jaafar; Zaki Aman, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Koperasi Penanam Sawit Mampan (KPSM) or in English known as Sustainable Oil Palm Growers Cooperative has been established since 2010. KPSM is an alternative model that can meet the needs of oil palm independent smallholders (ISH) and play a role in helping to improve community development. The main objective of this cooperative is to improve the income of independent oil palm smallholders. The objective of the implementation of the study was to identify the customer satisfaction level towards the FFB sales service operated by KPSM. This study involved independent oil palm smallholders who sent fresh fruit bunches (FFB) to KPSM cooperative collection centres. Questionnaires were distributed to 330 respondents and sampling was carried out by random sampling. The data were analysed using SPSS to analyse the quantitative data, which covered frequencies and percentages. The study findings indicated that the majority of respondents were KPSM members (61.9%), who cultivated palm full time, (69.6%) with an average age of 46 years old. The study also proved that the smallholders’ satisfaction level who received the services provided by the cooperative, was very good. However, customer satisfaction in terms of infrastructure amenities was less satisfactory, and the findings from this study were hoped to be able to assist various parties to improve the quality of services provided by KPSM.